Use of savolitinib as neoadjuvant therapy for non–small cell lung cancer patient with MET exon 14 skipping alterations: A case report - Zhang, Yu; Zhang, Hao; Wang, Hanqing; Zeng, Jingtong; Zhang, Bo; Zhou, Ning; Zu, Lingling; Song, Zuoqing; Wang, Changli; Xu, Song (Frontiers in Oncology, 2022)
Savolitinib is a tyrosine kinase inhibitor being developed for the treatment of metastatic non–small cell lung cancer (NSCLC) with mesenchymal–epithelial transition (MET) factor exon 14 skipping alterations. However, the role of savolitinib in neoadjuvant therapy for lung cancer remains unclear. Here, we present a case of a 65-year-old woman diagnosed with stage IIIA (cT2bN2M0, eighth TNM stage) upper right lung adenocarcinoma harboring MET exon 14 skipping alterations. After 4 weeks of therapy, a partial response was achieved with neoadjuvant savolitinib, and significant shrinkage in tumor and lymph nodes was observed. We also measured the immune microenvironment of the primary tumor pre- and posttreatment with savolitinib.